Design of 1-(furan-2-yl)-N-(5-substituted phenyl-1, 3, 4-thiadiazol-2-yl) methanimine derivatives as Enoyl-ACP reductase inhibitors: Synthesis, molecular docking studies and antitubercular activity (Bangladesh Journal of Pharmacology, 2013)
A series of 5-phenylsubstiuted 1, 3, 4 thiadiazoles clubbed with furan moiety (Fa-Fe) by means of azomethine linkage have been synthesized. All the newly synthesized compounds were characterized by IR,1HNMR and Mass analyses. All the synthesized molecules have been predicted as antitubercular in nature by PASS in silico approach. In vitro antitubercular screening was performed by alamar blue assay method on Mycobacterium tuberculosis H37Rv strain. Among the synthesized derivatives Fb and Fe were active at 3.125 µg/mL against M. tuberculosis H37Rv strain. The mechanism of action of the active compounds was carried out by docking of receptor enoyl-ACP reductase. It has been concluded that both Fb and Fe posses a significant interaction of hydrogen bonding and electrostatic attraction with Tyr 158 and Met103 in the active site of enzyme.